Effectiveness of The Interactive Media-Assisted Electrolysis Module on Students' Conceptual Understanding - Jurwita, Maghfira; Khaldun*, Ibnu; Winarni, Sri; Ahmad, Nur Jahan; Rahmi, Ayu; Habibati, Habibati (Jurnal Pendidikan Sains Indonesia, 2024)
Teaching materials are an important aspect of supporting the learning process. Modules can be used as an alternative that makes students play an active role in understanding chemistry learning concepts. Therefore, this research aims to develop a module assisted by interactive media and determine its feasibility in understanding students' concepts. Analyisis, design, development, implementation, dan evaluation (ADDIE) development model was utilized in the research, which was carried out utilizing a research and development (RD). The interactive media-assisted module was implemented employing a nonequivalent posttest-only control group design. Class XII students at MAS Ulumul Qur'an Langsa made up the study's population. The sample for this research is class data collection through validation sheets, test questions, and questionnaires. The results of the validity test show that the module developed is included in the valid and reliable category with an average content validaty index (CVI) assessment score of 1.00 and an inter-rater agreement (IRA) of 98.25%. The data analysis outcomes that come from comprehending the concept using the t test obtained a sig value. (2-tailed) 0.0000.05 indicates that there is a significant difference in conceptual understanding between students who use modules assisted by interactive media and those who use printed books. The results of this research show that this interactive media-assisted module is very suitable for use, so it can be concluded that using this module can increase students' understanding of concepts